Operation of an efficient site-specific recombination system of Zygosaccharomyces rouxii in tobacco cells. - Onouchi, H (1991)
Recombinase encoded by the R gene of pSR1 of Zygosaccharomyces rouxii mediates reciprocal recombination between two specific recombination sites (RSs) to induce excision or inversion of the DNA segment that is flanked by the RSs. We report here that site-specific recombination mediated by this system takes place effeciently in tobacco cells. To monitor the recombination events in tobacco cells, we have constructed two types of cryptic beta-glucuronidase reporter gene in such a way that recombination such as inversion of the construct or excision of the intervening sequence results in their expression. When these cryptic reporter constructs were transiently introduced together with the R gene by electroporation into protoplasts of tobacco cells, beta-glucuronidase activity was detected. The cryptic reporter genes, when stably resident in the chromosome of tobacco cells, were also activated by the R gene. Structural analyses of the genomic DNA isolated from these tobacco cells showed that the R protein did in fact catalyze precise recombination between two copies of RSs in tobacco cells, with resultant activation of the cryptic reporter genes. This observation provides the basis for development of a DNA technology whereby large regions of DNA can be manipulated in plant chromosomes. Potential uses of this recombination system are discussed.